2017
DOI: 10.1186/s13068-017-0733-0
|View full text |Cite
|
Sign up to set email alerts
|

Integrating enzyme fermentation in lignocellulosic ethanol production: life-cycle assessment and techno-economic analysis

Abstract: BackgroundCellulase enzymes have been reported to contribute with a significant share of the total costs and greenhouse gas emissions of lignocellulosic ethanol production today. A potential future alternative to purchasing enzymes from an off-site manufacturer is to integrate enzyme and ethanol production, using microorganisms and part of the lignocellulosic material as feedstock for enzymes. This study modelled two such integrated process designs for ethanol from logging residues from spruce production, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
51
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(53 citation statements)
references
References 54 publications
1
51
0
1
Order By: Relevance
“…Data regarding the environmental performance of the enzyme product were provided by the enzyme supplier after personal communication and were estimated to be 39 MJ of primary energy demand and 0.64 kg carbon dioxide equivalents (CO 2 eq) per kg of enzyme product. 29 These values are considerably lower compared to data found in previous publications 7,30,31 due to continuous process improvements as well as geographical variations in enzyme production. The current energy used during enzyme production in Denmark is primarily based on renewable sources.…”
Section: Pathway A: 2-eh Through Biomass Fermentation and Ethanolmentioning
confidence: 85%
“…Data regarding the environmental performance of the enzyme product were provided by the enzyme supplier after personal communication and were estimated to be 39 MJ of primary energy demand and 0.64 kg carbon dioxide equivalents (CO 2 eq) per kg of enzyme product. 29 These values are considerably lower compared to data found in previous publications 7,30,31 due to continuous process improvements as well as geographical variations in enzyme production. The current energy used during enzyme production in Denmark is primarily based on renewable sources.…”
Section: Pathway A: 2-eh Through Biomass Fermentation and Ethanolmentioning
confidence: 85%
“…However, environmental results are aligned with the cost of enzyme production. Other studies have demonstrated the implications that enzyme production has on total costs and emissions for the production of lignocellulosic ethanol . The further integration of enzyme production into the biorefinery is expected to result in a reduction of the total impacts aiming for a scenario in which total environmental burdens can be reduced.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have demonstrated the implications that enzyme production has on total costs and emissions for the production of lignocellulosic ethanol. 71 The further integration of enzyme production into the biorefinery is be used to determine the eco-efficiency of a product or process. In general, the environmental impact and value of the system are the general concepts analyzed.…”
Section: Enzyme Productionmentioning
confidence: 99%
“…TEAs and LCAs commonly incorporate uncertainties in performance indicators based on rough estimates of increasing or decreasing performance (Olofsson et al, 2017). Very few studies have based their uncertainty estimates on laboratory data (Vicari et al, 2012).…”
Section: Introductionmentioning
confidence: 99%